Vegetation communities and identification of indicator species in the riparian areas of Zabarwan mountain range in the Kashmir Himalaya - Shiekh Marifatul Haq (16538978) (2023)
Plant communities that occur along water corridors are termed riparian vegetation. Although relatively narrow and long, riparian zones do provide an extensive spatially linear network of connectivity between existing habitats, allowing species to move more easily in response to changing microclimate conditions. Knowledge of riparian ecosystems in the Himalayan Region of Kashmir has not been explored, even though this region is unique and comprises some of the most important hotspots for Himalayan biodiversity. The current study characterizes the vegetation community along a riparian ecosystem in the Zabarwan Range, where there is no information on community characterization. After preliminary surveys, the three sites representing the study area were selected for detailed field sampling (Community-1 at the lower end of the stream; Community-2 at the middle of the stream, and Community-3 at the upper end of the stream). Data on the communities were gathered using the T-transect vegetation sampling method, and indicator plant species along the riparian zones were identified using Analysis of Indicator Species (AIS). A total of 71 plant species were collected, which were divided into 64 genera and 38 families. With nine species, the Rosaceae family was the largest, followed by the Asteraceae with six species. Three community associations, Ulmus-Parrotiopsis-Oplismenus, Salix-Rosa-Oplismenus, Celtis-Viburnum-Fragaria, were identified on the basis of an important value index. Diversity indices show significant differences in riparian vegetation between the types of plant communities. Shannon Diversity was also found to be higher in communities 2 and 3, indicating that the vegetation there was more diverse. Ulmus villosa is a common indicator species in Community-1 and Community-2, while Prunus tomentosa is a common indicator species in Community-3 and Community-1. Rosa webbiana was found as an indicator species in Community-2 and Community-3 while Celtis australis and Viburnum grandiflorum were restricted to Community-3. The identified indicator species in the vegetation associations can be employed for restoring riparian zones because of their excellent ecological performance and capacity for regrowth in these environments. Other Information Published in: Environmental and Sustainability Indicators License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.1016/j.indic.2023.100277